The Lingua Franca Core (LFC) and Its Impact on Pronunciation Teaching Practice in Indonesia - Jaelani Jaelani (Humanitatis : Journal of Language and Literature, 2021)
English pronunciation is a crucial part of communication however, it can be overwhelmingly challenging for non-native speaker students. Phonologically, it is because of its inconsistent orthography and idiosyncratic phonetics; it is also idiosyncratic or distinctive and not universal. To overcome such problems, Jenkins proposes a Lingua Franca Core (LFC). Despite its potential benefits, the LFC is practically and administratively challenging to be implemented in pronunciation learning practice in Indonesia. Thus, aiming to find issues regarding LFC in pronunciation teaching practices in Indonesia, data generated from ten Indonesian educational practitioners with diverse language backgrounds are qualitatively analyzed in this study. This study indicates that, practically, the replacement of dental fricatives /θ/ and /ð/ and its replacements with labiodental fricatives /f/ and /v/ is a failed suggestion and might lead to the fossilization of these sounds. Also, the LFC in the sentence level of utterance might not be as significant as in the word level. Administratively, LFC is challenging because of teachers' limited knowledge, training, and sources regarding assessing students’ English pronunciation skills, teachers' and students’ attitudes toward certain English accents, and the fact that pronunciation is not explicitly being taught in English class in Indonesia.